Logical Thinking in Idealist and Rational Students - Agustina, Lady; Galatea, Chusnul Khotimah (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
The purpose of this study is to describe students’ logical thinking based on Keirsey’s personality types, specifically the Idealist and Rational types, within the topic of social arithmetic. The research adopts a descriptive qualitative approach. Data collection involves three techniques: MBTI (Myers-Briggs Type Indicator) surveys, logical thinking written tests, and semi-structured interviews. The study participants consist of students from classes VII A, VII B, and VII C at SMP Muhammadiyah 9 Watukebo. The research subjects include four students: two with Idealist personality types and two with Rational personality types according to Keirsey’s classification. The findings indicate that none of the research subjects fully meet the three logical thinking indicators, which are grouped into six points. However, there is one indicator that all subjects were able to achieve: the first indicator related to coherence of logical thinking (point B), which involves expressing the general steps used in problem-solving. On the other hand, there are indicators that none of the research subjects were able to fulfill completely. These include the second indicator concerning argumentation ability (point A), which involves articulating the logical reasons for using general steps in problem-solving, and point C, which pertains to expressing the logical reasons behind the correct final answer. Among the research subjects, the subject who successfully fulfills the good logical thinking indicator is the second subject with a rational personality type according to Keirsey’s classification.